Analysis of the effect of fly ash on the strength and cost of recycled aggregate concrete in the Philippines - Alipio, Aloysius Kristoffer; Raquino, John Carlo G. (College of Engineering, University of the Philippines Diliman, 2016)
The Philippines, being a developing country, produces large quantities of construction and demolition waste. The construction of modem concrete structures in the country also requires massive amounts of raw materials like aggregates and cement. At present, there are no existing C&D waste management systems in the Philippines, thus leading to C&D waste being underutilized and mostly being thrown in landfills or used as subgrade in road pavement. Several studies have shown that up to 30% of the natural aggregate component of concrete may be replaced by Recycled Concrete Aggregates (RCA). The study aims to determine the possible effects of adding ny ash, to both the strength and cost of Recycled Aggregate Concrete (RAC). Recycled Concrete Aggregates were collected from two demolished sites. A comparative analysis of the 7-day and 28-day compressive strengths of several concrete mixes of 30% RCA, with varying fly ash contents (0%, I 0%,30%,50%,70%), was investigated. The results of the study show that the workability of RAC increases as the fly ash content increases, and the compressive strength of the samples increased as the fly ash replacement increases up to 30% and decreases thereafter. A cost comparison was also done between concrete made with (I ) normal aggregates, (2) normal aggregates and RCA, and (3) normal aggregates, RCA and fly ash. The results show that the maximum feasible cost for the use and production of RCA increases as the amount offly ash used in the mix increases. The research suggests an optimum fly ash replacement ratio of 10% based on the increase in strength and decrease in cost for samples from both sites.